2022
DOI: 10.1007/s00296-022-05267-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of complementary and alternative medicine methods in the management of ankylosing spondylitis, rheumatoid arthritis, and fibromyalgia syndrome

Abstract: A wide variety of musculoskeletal, arthritic, connective tissue, and vasculitic diseases fall under the umbrella of "rheumatic diseases". Ankylosing spondylitis, rheumatoid arthritis, and fibromyalgia syndrome are the three members of this disease group with relatively high prevalence. Pharmacological options are at the center of therapeutic algorithms in treating rheumatic diseases, particularly in reducing inflammation. Despite significant advances in pharmacological treatment in recent years, achieving comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…A growing number of patients are turning to CM [10]. The burden of MSK diseases has increased substantially from 2000 to 2015, with MSK diseases being the second leading cause of years lived with disability worldwide [19], Possible explanations might be the current increase in average life expectancy coupled with the fact that many degenerative MSK diseases are largely irreversible [20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A growing number of patients are turning to CM [10]. The burden of MSK diseases has increased substantially from 2000 to 2015, with MSK diseases being the second leading cause of years lived with disability worldwide [19], Possible explanations might be the current increase in average life expectancy coupled with the fact that many degenerative MSK diseases are largely irreversible [20].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also demonstrated similar findings where nutritional CM was more common than physical CM or combined forms. This could be because oral medicine is self-administered, potentially less expensive, and more easily accessible [10,24]. Almost all the study patients reported using nutritional or physical CM in conjunction with their prescribed treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations